X.25 traffic generator - Aspin, SJ (Department of Electrical Engineering, 2016)
Due to the lower cost and error free data transmission capabilities offered by packet switching, numerous countries have installed national packet switched networks. The South African packet network, SAPONET-P, became operational in 1982 and has been growing rapidly, creating a need for network test equipment. This thesis describes the design of a high speed traffic generator which can be used to test and monitor the throughput capabilities of equipment or part of the network as a whole. To meet the main requirement of the traffic generator, that it should support a number of high speed X.25 lines, a multiprocessor architecture was chosen to cope with the high data throughput. An IBM PC was used as the base system, with several specially designed X.25 cards being installed in its expansion slots. The major part of the work done was on the design and development of the X.25 cards, each of which provides two high speed (64 Kbps) X.25 links. In order to achieve this throughput, the card uses three processors coupled on a local bus to a 256K multi-port memory. Two WD25ll processors implement the link level of the X.25 packet switching protocol (LAPB), with the required software being micro-encoded on the chip. An 8088 processor, the same as is used in the PC, implements the packet level, the traffic generator and overall control of the card. Extensive use was made of programmable array logic (PAL) devices to implement the system logic required. All programs for the traffic generator are written in the modern and powerful c language which is ideally suited to the application. The software was written in a modular fashion with the various modules being linked together by means of a set of common data structures. Use was made of packet buffers and job queueing to allow the traffic generator to cope with very high peak data rates. As well as programs for the X.25 cards, a monitor program runs on the PC and allows the· user to view statistics screens and modify the traffic generator configuration. While primarily designed for the,traffic generator application, the X.25 card may also be configured for a variety of other networking applications. By substituting a local area network (LAN) processor for the X.25 one, the card can be used as a low cost network card or as a network file server. The card can also be configured to provide a low cost means of connecting a PC based workstation to the packet switching network. As all programs are downloaded onto the cards from the PC, it is relatively easy to modify or upgrade the software. Thus while meeting the original project requirements, the traffic generator design has a flexible and expandible nature.